2021
DOI: 10.20525/ijfbs.v10i1.1064
|View full text |Cite
|
Sign up to set email alerts
|

Fiscal Deficit and its effects on economic growth

Abstract: The main purpose of this paper is to assess the impact of the deficit on GDP growth for the Eurozone area, using panel data for a period from 1995 to 2015, with a total of 257 observations. In order to conduct the study and come up with results, we have used a multiple linear regression model with the least-squares regression. Consequently, in order to test the data used in the model, we have applied diagnostic tests, such as the Durbin-Watson test to analyze the correlation of serial correlation, as well as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…Their study also witnessed that there is a bi-directional causality between budget deficit and economic growth. Similarly, the work of [ 35 ] Found that fiscal deficit has a positive relationship with the economic growth for the panel of Eurozone countries during the study periods of 1995 to 2015. Employing the multiple linear regression estimation technique, their study found that long deficits are harmful compared to short deficits in the study area during the period under investigation.…”
Section: Literature Reviewmentioning
confidence: 79%
“…Their study also witnessed that there is a bi-directional causality between budget deficit and economic growth. Similarly, the work of [ 35 ] Found that fiscal deficit has a positive relationship with the economic growth for the panel of Eurozone countries during the study periods of 1995 to 2015. Employing the multiple linear regression estimation technique, their study found that long deficits are harmful compared to short deficits in the study area during the period under investigation.…”
Section: Literature Reviewmentioning
confidence: 79%
“…In a similar vein, the findings of this study, such as those of Navaratnam and Mayandy (2016), showed that the fiscal deficit has a negative influence on economic growth in all of the South Asian nations included in this study, with the exception of Nepal, where the results showed a positive impact. Additionally, some literature also confirmed that the fiscal deficit is positively influenced the economic growth (Aslam, 2016;Kryeziu and Hoxha, 2021).…”
Section: Brief Literature Reviewmentioning
confidence: 85%
“…The prior studies give results, like, Nayab (2015) found that FD does not affect GDPg in the case of Pakistan, Rahman (2012) in the case of Malaysia, and Thirunavukkarasu and Achchuthan (2013) in the case of Sri Lankan. However, Ahmad (2013) found that there is a positive link between FD and GDPg in the case of Pakistan, Kryeziu and Hoxha (2021) in the case of Eurozone, Qehaja-Keka et al (2023) in the case of Eurozone countries, and Pelagidis and Desli (2004) in case of some European countries. However, Tung (2018) concluded that FD had harmful effects on GDPg in the case of Vietnam, Hassan and Akhter (2014) in the case of Bangladesh, Navaratnam and Mayandy (2016) in case of the countries of South Asia and Nepal the impact was positive and Iqbal et al (2017) in the case of Pakistan.…”
Section: Regression Resultsmentioning
confidence: 99%
“…Further investigation into the influence of the budget deficit on real GDP demonstrates that the Keynesian theory is applicable in Malaysia. Kryeziu and Hoxha (2021) used Eurozone data from 1995-2015 and employed an OLS to carry out the investigation and provide the findings. They show that increasing the deficit ratio to GDP has a beneficial influence on the GDPg.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation